PENGARUH PROFITABILITAS DAN KEBIJAKAN DEVIDEN TERHADAP RETURN SAHAM - Diah Nurdiana, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
This study aims to analyze the effect of profitability and dividend policy on stock returns. The independent variable used is Return On Equity (ROE) and dividend payout ratio (DPR). The dependent variable used is stock return. The population in this study is LQ 45 companies listed on the Indonesia Stock Exchange (IDX) in the 2013-2017 period. Samples collected using purposive sampling method. The number of samples is 7 LQ 45 companies listed on the Indonesia Stock Exchange for the period 2013-2017. Analysis of the data used to test the hypothesis is to use simple regression analysis techniques and multiple regression analysis. Based on the results of the study shows that (1) Profitability does not have a significant effect on stock returns. (2) Dividend policy has a positive and significant effect on stock returns. (3) Profitability and Dividend Policy jointly have no significant effect on Stock Returns